Ways on how to connect with alumni / Aeimysyariza Sahya - Sahya, Aeimysyariza (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Higher education students look forward to graduation because it gives them a sense of success and gives them hope for the future. The university still has work to perform once students leave and become alumni. A thriving community supports flourishing colleges, and developing that community begins with innovative alumni management. It’s crucial to involve recent graduates in your alumni programme as soon as feasible. If alumni get involved when they still have a strong sense of personal connection to the university, they are more inclined to contribute to the developing community as they move forward in their life. Alumni from universities can be a wonderful source for fundraising, student retention, and job networking. However, you need to take care of your relationship with them. So, here is some tips on how to connect with the alumni.